(Studi Toksisitas Akut dan Subakut dari Ekstrak Minyak Buah Merah pada Tikus Sprague Dawley) - Toshiaki Nishigaki; Fitriya N.A. Dewi; Hendra Wijaya; Hidekazu Shigematsu (Warta Industri Hasil Pertanian, 2011)
Pandanus conoideus is exclusively grown in papua island and its neighbor areas and its fruit (buah merah) has been utilized as food supplement by the native papua people for a long period. recently it was found that its extract oil (SMB) contains contents of carotenoids ,especially a novel micronutrient beta-cryptoxanthin .we consider that SBM is a potent chemopreventive supplement against some types of cancer and provide health benefits for chronic diseases .in the present studies, we evaluated acute ad subacute toxicities of SBM using Sprague Dawley rats.Oral acute toxicity of SBM using female rats was not observed and LD 50 was more than 2 ml/kg in subacute toxicity study ,SMB was orally administered at 0.1,0.3 and 1.0 ml/kg to male and female rats for consecutive 4 weeks .no findings associated with SBM observed we consecutive 4 weeks .no findings associated with were observed we conclude that SBM is a safe food supplement.